Carbon uptake and water productivity for dry-seeded rice and hybrid maize grown with overhead sprinkler irrigation - Alberto, Ma. Carmelita R.; Buresh, R.J.; Hirano, Takashi; Miyata, Akira; Wassmann, Reiner; Quilty, J; Correa, T.; Sandro, J (Elsevier, 2013)
A growing scarcity of irrigation water could progressively lead to changes in rice production to systems using less irrigation water for rice or more crop diversification. A shift from current production of rice on flooded soils to production of rice on non-flooded soil with water-saving irrigation or to production of more water-efficient crops will have profound effects on carbon, water, and energy exchanges. This study used the eddy covariance technique to examine C uptake and water use efficiencies for water-saving, dry-seeded rice production and production of hybrid maize under overhead sprinkler irrigation as an alternative to flooded rice during two growing seasons. Maize with its C4 physiology has greater photosynthetic capacity than rice. In 2011, maize had 1.4 times higher net C uptake than rice and twice as much grain yield as rice (10.4 vs 5.3 Mg ha−1). In 2012, lower solar radiation due to increased cloudiness and heavy rainfall during critical growth stages (late vegetative to early reproductive) decreased LAI and resulted to about 20% less net C uptake and maize yield (8.2 Mg ha−1), but the rice yield was unchanged (5.3 Mg ha−1) presumably because of improved crop management which included effective crop establishment at lower seed rate and efficient N application using fertigation. Canopy light use efficiency, crop water productivity (WPET), and photosynthetic water use efficiency were 1.8, 1.9, and 1.6 times higher for maize than rice, respectively, despite sensitivity of maize to excess water. Net C uptake, evapotranspiration, and WPET of dry-seeded rice under overhead sprinkler irrigation were comparable to those reported elsewhere for flooded rice. Average total water input (irrigation + rainfall) for rice was only 908 mm, as compared to 1300–1500 mm reported in literature for typical puddled transplanted rice.